The R2R3-MYB transcription factor ThRAX2 recognized a new element MYB-T (CTTCCA) to enhance cadmium tolerance in Tamarix hispida. (April 2023) - Wang, Yuanyuan; Wu, Jing; Li, Jinghang; Liu, Baichao; Wang, Danni; Gao, Caiqiu
Abstract: R2R3-MYB transcription factors play an important role in plant development and response to various environmental stresses. In this study, a new R2R3-MYB gene, named ThRAX2, was isolated from T. hispida . ThRAX2 has an open reading frame (ORF) of 1191 bp and encodes a protein of 396 amino acids. ThRAX2 was localized in the nucleus. The overexpression of ThRAX2 in Arabidopsis and T. hispida significantly increased Cadmium (Cd) tolerance. Moreover, the accumulation of cadmium in roots and leaves was significantly reduced. The TF-centred Y1H and Y1H results showed that ThRAX2 was able to specifically bind a new cis-element (MYB-T, CTTCCA). The promoters of some Cd-responsive genes, such as ThSOS1, ThCKX3, ThCAX3A, ThMYB78, ThMIP2, ThTPS4, and ThSOD2, all contained 1–3 MYB-T sequences. Furthermore, chromatin immunoprecipitation-polymerase chain reaction (ChIP-PCR) and ChIPquantitative (q)PCR showed that the ThRAX2 gene can bind to ThSOS1, ThCKX3, ThCAX3A and ThMYB78 promoter fragments, including the MYB-T motif. Meanwhile, the qRTPCR results also showed that the expression trends of ThSOS1, ThCKX3, ThCAX3A and ThMYB78 were similar to that of ThRAX2 . This finding suggests that Cd tolerance of the ThRAX2 gene may regulate the expression of some downstream genes through specific recognition of the MYB-T motif and participate in regulating intracellular ion homeostasis, transport, and protein activity or enhance antioxidant enzyme activity. This study found a novel cis-acting element that binds ThRAX2 to regulate Cd tolerance, which lays the foundation for the ThRAX2 regulatory mechanism of Cd stress. This study provides a genetic and theoretical basis for the bioremediation of Cd-contaminated land by cultivating transgenic plants in the future. Highlights: Overexpression of ThRAX2 significantly increased Cd tolerance. ThRAX2 was able to specifically bind a new cis-element (CTTCCA). ThRAX2 gene can bind to 4 genes promoter fragments including the CTTCCA motif.